Localisation and significance of in vivo near-infrared autofluorescent signal in retinal imaging. Issue 8 (29th September 2010) - Schmitz-Valckenberg, Steffen; Lara, David; Nizari, Shereen; Normando, Eduardo M; Guo, Li; Wegener, Alfred R; Tufail, Adnan; Fitzke, Fred W; Holz, Frank G; Cordeiro, M Francesca
Abstract : Aim: To evaluate near-infrared (NIR) autofluorescence (AF) in patients with geographic atrophy (GA) secondary to age-related macular degeneration and to investigate the origin of the signal by in vivo and histological analysis in rats and in a human donor eye. Methods: Confocal scanning laser ophthalmoscopy in vivo imaging, including blue (excitation: 488 nm, emission 500–700 nm) and NIR (excitation: 790 nm, emission >810 nm) AF was performed in 21 eyes of 18 GA patients. Pigmented and albino rats underwent with the same device both in vivo and post-mortem imaging. For the latter, cryostat prepared retinal cross-sections were imaged using an additional customised magnification lens. Finally, cross-sections of a 49-year old human donor eye were recorded. Results: Atrophic areas in GA were characterised by low NIR AF intensities. In the junctional zone of atrophy, focal areas of increased intensity were seen which appeared to seldom correlate to blue AF findings. Confocal live scanning in pigmented rats identified the maximum of the NIR AF signal in the outer retina, with histological confirmation of the signal origin localised to the retinal pigment epithelium and sclera in both animals and human donor eye. No NIR AF was found in the retina of young non-pigmented rats. Discussion: This study further underscores the assumption that melanin is the main source of NIR AF in the healthy retina. Increased NIR AF intensities in the junctional zone in GA may represent accumulation of melanolipofuscin, which may reflect disease activity and thus may allow for early identification of patients at high-risk of GA enlargement.